Efficacy of pediatric acute pancreatitis scores at a Japanese tertiary center. Issue 3 (16th December 2015) - Hashimoto, Naoya; Yotani, Nobuyuki; Michihata, Nobuaki; Tang, Julian; Sakai, Hirokazu; Ishiguro, Akira
Abstract: Background: Pediatric acute pancreatitis (AP) is a rare but important clinical entity associated with significant morbidity. Predicting the severity and outcome of AP in pediatric patients can be challenging because there are few validated severity scoring systems. Moreover, the etiology of pediatric AP in the Japanese population is different from that of Western populations. The performance of severity scores in pediatric AP with a high prevalence of severe cases is still unknown. The aim of this study was to assess the performance of existing severity scoring systems when used for Japanese children at a tertiary care center. Methods: We reviewed the electronic medical records of all children (≤18 years) treated for AP at between 2002 and 2012 at National Center for Child Health and Development, Tokyo. The modified Glasgow acute pancreatitis severity score (modified Glasgow), Ranson criteria (Ranson), Balthazar computed tomography severity index (CTSI), and pediatric acute pancreatitis severity (PAPS) score were assessed for their ability to distinguish severe pancreatitis from the milder forms. Results: Thirty‐three Japanese children with AP were identified. Among them, 37 episodes were analyzed for the performance of the scoring systems and 33 for the etiology. The most common etiology of AP was structural abnormality ( n = 8). Sensitivity for the modified Glasgow, Ranson, PAPS, and CTSI was 42.9%, 52.4%, 81.0%, and 50.0%, respectively, while specificity was 81.3%, 81.3%, 37.5%, and 76.9%, respectively. Conclusion: We found PAPS to be the most reliable when used for discriminating the severe form of AP from the milder forms at a Japanese tertiary pediatric care center.